Literature review on pressure–velocity decoupling algorithms applied to built-environment CFD simulation - Wang, Haidong; Wang, Hui; Gao, Feng; Zhou, Pengzhi; Zhai, Zhiqiang (John) (Building and environment, 2018)
For decades, computational fluid dynamics (CFD) has been applied to built-environment related simulations such as those of building ventilation, indoor airflow, and contaminant transportation. The pressure–velocity decoupling algorithm employed in CFD to solve momentum equation(s) exerts significant influence on the convergence speed and computational resource requirement. In order to identify the opportunities to improve CFD performance for built-environment simulation, a review is conducted on the commonly used pressure–velocity decoupling algorithms in indoor environment CFD modeling, with the aim of summarizing the general status and trends of the application and development of the decoupling algorithms. The study categorizes the primary algorithms based on the advantages and disadvantages of each reviewed algorithm and the applications of each analyzed algorithm. The review indicates an explicit prevalence of the usage of the SIMPLE algorithm and its variants in indoor-environment CFD simulation, which is a combined outcome of the superiority of such algorithms and their wide availability in commonly used CFD software. However, each algorithm variant has applicable engineering fields unique to it. The study also identifies that a few less-commonly used algorithms in both research and commercial CFD software, such as the projection algorithm, reveal certain advantages in terms of convergence and accuracy performance. These algorithms exhibit significant potential for transforming the conventional pressure–velocity decoupling algorithm into approaches that can more efficiently solve flow-governing momentum equation(s), specifically for built-environment CFD simulation. •Prevalent pressure-velocity decoupling algorithms used in built-environment simulations are reviewed and categorized.•Less commonly used algorithms are identified to reveal their specific advantages.•Potential directions for pressure-velocity decoupling algorithm development in built-environment simulation are discussed.